Analysis of Green Open Space Needs in Bogor City - Irfan Ihsani; Fulki Dwiyandi Araswati (Universitas Medan Area, 2023)
The availability of green open space (GOS) especially in urban areas, is very important considering the large benefits obtained from GOS. GOS is a land (area) overgrown with green plants and plays an important role in maintaining natural ecosystem balance in urban areas. The area used as GOS can be a park, field, or green path on the side or in the middle of the road. This study aims to determine acreage of GOS changes and its adequacy based on population and area in Bogor City. The scope of this study is the South, Central and East Bogor Districts. The analysis technique used is spatial analysis using ArcGIS 10.3 software. The results showed that in 2009 the GOS in South, Central and East Bogor Districts was 1982,23 Ha and 1197,49 Ha in 2021 or it was a decline at about 784,74 Ha during the period. Based on population number in 2021 South, Central and East Bogor Districts needs GOS of 809,05 Ha.